2018
DOI: 10.1364/oe.26.006560
|View full text |Cite
|
Sign up to set email alerts
|

High-repetition-rate, high-pulse-energy, and high-beam-quality laser system using an ultraclean closed-type SBS-PCM

Abstract: We present a high-repetition-rate, high-pulse-energy, high-beam-quality, and high-average-power laser system using an ultraclean closed-type stimulated-Brillouin-scattering phase-conjugate mirror (SBS-PCM). By controlling microparticles of SBS-PCM down to 40 nm, thermal load capacity of such closed-type SBS-PCM was greatly improved, which presented the best reported cleanliness. The closed-type SBS-PCM, lacking scanning wedge plates, achieved reflectivity as high as 92% and showed no optical breakdown phenomen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Scientific researchers in China have performed well at this stage. As shown in figure 5(a), the SBS-based phase conjugation mirror (PCM) is used to compensate for the wavefront distortion caused by optical defects and thermal distortion, so as to obtain high-quality beam output [33]. In the process of opposite propagation between Stokes and pump, the self-amplification effect of SBS makes the pulse width of the Stokes significantly compressed compared with the pump, as shown in figure 5(b).…”
Section: Statusmentioning
confidence: 99%
“…Scientific researchers in China have performed well at this stage. As shown in figure 5(a), the SBS-based phase conjugation mirror (PCM) is used to compensate for the wavefront distortion caused by optical defects and thermal distortion, so as to obtain high-quality beam output [33]. In the process of opposite propagation between Stokes and pump, the self-amplification effect of SBS makes the pulse width of the Stokes significantly compressed compared with the pump, as shown in figure 5(b).…”
Section: Statusmentioning
confidence: 99%
“…In SBS pulse compression, the liquid medium used for Brillouin scattering has the advantages of no high pressure, a small absorption coefficient, and a high laser damage threshold compared with gas and solid media, and is most suitable for SBS with high injection energies and long interaction distances [9][10][11][13][14][15][16]. Therefore, SBS pulse compression based on the liquid medium is the most promising technical method for obtaining a high-energy sub-nanosecond laser with a kilohertz-level repetition rate.…”
Section: Introductionmentioning
confidence: 99%
“…The effective thermal mitigation methods in the literature can be divided into two categories. The first is the liquid purification method to remove large impurity particles in the liquid medium [ 16 , 28 ] , which can appropriately reduce the total heat absorption generated by the laser absorption within the medium and reduce the optical-breakdown probability. The second category is the method involving flowing liquid and a wedge-based moving focal spot [ 27 , 29 ] , which are used to alleviate the local focusing heat accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…By appropriately using SBS-PCMs, except for realizing picosecond pulses, one can also compensate wavefront distortions caused by optical elements during laser transmission and amplification processes, leading to a higher beam quality output [25,26]. For this reason, today, the combination of SBS-PCMs and master oscillator power amplifier (MOPA) is a common method to achieve high peak power, high beam quality, and narrow pulse width lasers [27]. Although showed that the distortion with vortex wavefront will lead to the input "donut-like" pump pluses into peta-like Stokes pluses [28], SBS is always the most effective phase conjugation method for conventional lasers with the fundamental (i.e., TEM 00 ) spatial mode.…”
Section: Introductionmentioning
confidence: 99%